Pengaruh ROA, ROE, EPS, & PBV terhadap Stock Price dan Stock Return - Stephen Harlan; Henryanto Wijaya (Jurnal Ekonomi, 2022)
The purpose of this study is to determine the effect of Return on Assets (ROA), Return Equity (ROE), Earning per Share (EPS), and Price per Book Value (PBV) on stock prices and stock returns in manufacturing companies registered on the Indonesia Stock Exchange in 2018-2020. This study used 73 manufacturing companies as the sample and using panel data regression analysis. The results indicate that ROA has negative and insignificant effect on stock prices, and has positive and significant effect on stock returns; ROE has insignificant positive effect on stock prices, and has significant and negative effect on stock returns; EPS has negative and insignificant effect on stock prices, and has positive and insignificant effect on stock returns; PBV has negative and insignificant effect on stock prices, and has positive and insignificant effect on stock returns. ROA, ROE, EPS, and PBV simultaneously have significant effect on stock price and stock return.